Magnetic control of cellular processes using biofunctional nanoparticles. Issue 11 (15th September 2017) - Monzel, Cornelia; Vicario, Chiara; Piehler, Jacob; Coppey, Mathieu; Dahan, Maxime
Abstract : Remote control of cellular functions via mechanical, thermal or molecular stimulation is accomplished using biofunctional magnetic nanoparticles (MNPs) and magnetic fields. Abstract : Remote control of cellular functions is a key challenge in biomedical research. Only a few tools are currently capable of manipulating cellular events at distance, at spatial and temporal scales matching their naturally active range. A promising approach, often referred to as 'magnetogenetics', is based on the use of magnetic fields, in conjunction with targeted biofunctional magnetic nanoparticles. By triggering molecular stimuli via mechanical, thermal or biochemical perturbations, magnetic actuation constitutes a highly versatile tool with numerous applications in fundamental research as well as exciting prospects in nano- and regenerative medicine. Here, we highlight recent studies, comment on the advancement of magnetic manipulation, and discuss remaining challenges.